The early warnings of balance-of-payments problems: Kaminsky and Reinhart revisited - Michael Lang (Frankfurt School of Finance & Management, 2013)
This paper builds upon the model of Kaminsky and Reinhart (1999) and extends it to triplecrises. It applies a new visualisation approach combining elements of an event study analysis and a fan chart technique. This approach illustrates the deviation of fundamentals in the runup to balance-of-payments problems. The results suggest that both systemic banking crises and deteriorating government finances are highly significant leading indicators. Taking these indicators into account helps build a new early warning system for currency crises. The results are highly significant and robust. The out-of-sample forecasts demonstrate the strong predictive power of the model.
Keywords: F30; F31; F34; F41; G01; 330; currency crisis; financial sector vulnerability; early warning system